Peran Konselor dengan Pendekatan CBT Coach terhadap Self Esteem Mahasiswa Orang Kurang Upaya (OKU) di Universitas Awam Selangor, Malaysia - Lestari, Chika; Ridayana, Weny; Bitarsa, Aby Sefwiedtry; Monalisa, Monalisa; Abdullah, Muhammad Saffuan (Jurusan Bimbingan dan Konseling Islam, 2025)
Self-esteem is one of the most important parts of the human self. For students, of course self-esteem affects their daily lives. Students with good self-esteem will feel more meaningful in their lives than students who have low self-esteem. This research aims to determine the self-esteem picture of students who are members of the OKU community, a public university in Selangor, Malaysia through the role of counselors using the CBT Coach approach. This research uses a descriptive quantitative method with a pre-test exam, then observing the intervention carried out by the counselor using the CBT Coach approach to the OKU students. After that, to see the results, a post-test is given. The research results showed that there was an increase in self-confidence and positive attitudes of OKU students after being given intervention by the counselor. The pre-test results show that the majority of OKU students lack self-confidence and feel unsure that they will be appreciated by others. Therefore, the intervention provided by counselors using the CBT Coach approach is considered quite effective in increasing OKU students' self-esteem.